SINESTESIA BAHASA MELAYU RIAU SUBDIALEK KECAMATAN PANGEAN - Novia Oktari Yulanda; Charlina; Mangatur Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the patterns and meanings of the synesthesia of the Riau Malay language Subdialect of Pangean District spoken by the people of Pangean District. The benefits of this research are (1) theoretically, this research is expected to expand the reader's knowledge about semantics, especially about the change in meaning regarding synesthesia (2) practically, the results of this research can be useful to find out various patterns of eating changes and their meanings, especially in the Riau Malay Subdialect of Pangean District. The data and data sources obtained in this study are in the form of community speech in Pangean District, especially in Pauh Angit Hulu village which contains synesthesia in daily communication. The data collection techniques in this study are listening, recording and recording techniques. The data in this study was analyzed using qualitative descriptive techniques. The method used is descriptive in the form of words and language. The data analysis technique in this study uses data reduction techniques, data presentation, conclusion drawing and data verification. Based on the results of the study, the pattern of synesthesia in the Riau Malay Subdialect of Pangean District consists of 8 patterns, namely, (1) the pattern of the sense of sight to the sense of hearing, (2) the pattern of the sense of taste to the sense of sight, (3) the pattern of the sense of taste to the sense of hearing, (4) the pattern of the sense of touch to the sense of hearing, (5) the pattern of the sense of smell to the sense of sight, (6) the pattern of the sense of smell to the sense of sight, (7) the pattern of the sense of touch to the sense of sight, (8) the pattern of the sense of hearing to the sense of sight. The meaning of synesthesia in the Riau Malay Subdialect of Pangean District was found to have a connotative meaning. Connotative meanings are found in 3 forms, namely, (1) positive connotative meaning, (2) negative connotative meaning, (3) neutral connotative meaning.